India and the Gulf - I P Khosla Ed; KHOSLA (I P) Ed. (Delhi Konark Publishers Pvt Ltd, 2009)
About the Book: India And The Gulf The revolution in Iran, the Iraq-Iran war, the Soviet occupationof Afghanistan, then 9/11 and the US military actions inAfghanistan and Iraq-have put the Gulf and its surroundings high onthe international agenda. India has shown that it is prepared todevelop relations with the countries of the region in recognitionof their high importance. The question that needs to be examined indepth and detail is that in the light of our ancient cultural,trade and other contacts how exactly would Indias interests figurein all these contemporary developments and what should she do topromote those interests. In this volume, leading experts, analystsand academics examine different aspects of this question with aview to finding answers.
Keywords: International Relations; Middle East-Persian Gulf Region